Hubungan Peran Penyuluh Pertanian dalam Efektifitas Penyaluran Pupuk Bersubsidi Petani Padi Sawah di Kabupaten 50 Kota, Sumatera - Sari, Nila; Marta, Andrik; Afner, Syintia Ona Guserike (Universitas Galuh, 2026)
Subsidized fertilizer is one of the important instruments in government policy to increase agricultural production, especially rice paddy in maintaining national food security. The purpose of this study is to analyze the relationship between the role of farmer groups and extension workers in the distribution mechanism of subsidized fertilizer in 50 Kota Regency (Case Study: Harau District). The research method is a survey in Harau District, 50 Kota Regency. The number of respondents is 65 rice paddy farmers who are members of farmer groups. Primary data collection includes farmer characteristics, the role of extension workers and the role of farmer groups with data collection techniques through interviews, observations and questionnaires. Data analysis is descriptive quantitative with bivariate correlation analysis test (SPSS.20). The results of the study show that the distribution of subsidized fertilizer to farmers through 1) Data Collection and Verification, 2) Preparation of RDKK, and 3) Distribution Supervision. These stages are carried out in farmer groups and accompanied by agricultural extension workers. The relationship between the roles of farmer groups in subsidized fertilizer distribution shows that, in the context of subsidized fertilizer distribution, the role of field extension workers does not always reinforce each other across their dimensions. Their role as communicators, which emphasizes information delivery and policy dissemination, sometimes aligns with their role as motivators, which emphasizes coaching, encouragement, and empowering farmers to be active in the fertilizer distribution process.